SEISMIC ACTIVITY OF MOUNT EREBUS IN 1987 - カミヌマ, カツタダ; ムラカミ, カツミ; KAMINUMA, Katsutada; MURAKAMI, Katsumi (National Institute of Polar Research, 1989)
P(論文) In 1987,five seismic stations were operated in the summit area and on the flanks of Mount Erebus (77°37′S, 167°09′E, 3794m) and one station at the summit of Mount Terror in Ross Island, Antarctica. Two stations (TRC and E1) in the summit area out of five were operated well throughout the year. Therefore the hypocenters of only 48 earthquakes were determined using the seismic phase readings at five stations in 1987. The earthquakes are localized around the summit region. The averaged daily count of earthquakes at TRC is 64. This is reduced to 16 for HOO which is located on the flank of Mount Erebus. The daily numbers before 1986 were counted at HOO. The seismic activity around Mount Erebus in 1987 was as low as that in 1985 and 1986,and the trend of the low seismic activity lasted after the 1984 volcanic activity. departmental bulletin paper